Imaginary Axis As A Basic Morphology In The City Of Yogyakarta - Indonesia - Karsono, Bambang; Wahid, Julaihi (2008)

(untitled)
The life and characteristic of the cities in Indonesia cannot be separated by the influence of city’s development in Java Island.